Biodelivery of therapeutic extracellular vesicles: should mononuclear phagocytes always be feared? - Cieślik, Martyna; Bryniarski, Krzysztof; Nazimek, Katarzyna (Frontiers in Cell and Developmental Biology, 2023)
At present, extracellular vesicles (EVs) are considered key candidates for cell-free therapies, including treatment of allergic and autoimmune diseases. However, their therapeutic effectiveness, dependent on proper targeting to the desired cells, is significantly limited due to the reduced bioavailability resulting from their rapid clearance by the cells of the mononuclear phagocyte system (MPS). Thus, developing strategies to avoid EV elimination is essential when applying them in clinical practice. On the other hand, malfunctioning MPS contributes to various immune-related pathologies. Therapeutic reversal of these effects with EVs would be beneficial and could be achieved, for example, by modulating the macrophage phenotype or regulating antigen presentation by dendritic cells. Additionally, intended targeting of EVs to MPS macrophages for replication and repackaging of their molecules into new vesicle subtype can allow for their specific targeting to appropriate populations of acceptor cells. Herein, we briefly discuss the under-explored aspects of the MPS-EV interactions that undoubtedly require further research in order to accelerate the therapeutic use of EVs.